Talking with patients : keys to good communication - Myerscough, Philip R.; Ford, Michael J. (Oxford medical publications, 1996)
A compact source of information on communication skills for physicians and medical students, which includes hints on body language and advice on talking to a variety of specialized patients, including the terminally ill. The practical importance of communication is outlined.